Form and Function of the Yorùbá HTS (High Tone Syllable) Revisited: Evidence From Ìgbò Second Language Learners of Yorùbá - Oshodi, Boluwaji (El Colegio de México, A.C., 2016)
The HTS (High Tone Syllable), a v-shaped element that occurs between the subject noun phrase and the verb phrase in declarative sentences, remains unarguably a most controversial element in the grammar of Yorùbá language, as scholars have expressed contradictory opinions on its precise form and function. This study examines the HTS from the standpoint of second language acquisition with data collected through oral production from three Igbo native speakers (one child and two adults) who were Yorùbá L2 learners. It was discovered that the element has the unvarying form o with a high tone (ó ) and it usually and persistently occurs before verbs, and also appears to indicate tense and aspect in their interlanguage. The study concludes that, though the actual syntactic function of the HTS still remains controversial, evidence from Igbo L2 Yorùbá learners supports the fact that the element functions more like a tense and aspectual marker which indicates past/present actions in the language, as suggested by Awóbùlúyì (1992). Original received: 2015/02/27Review sent to author: 2015/07/03Accepted: 2015/07/08